Occurrence of Phyllostomus elongatus (Geoffroy St.-Hilaire, 1810) (Chiroptera, Phyllostomidae) in the Cerrado of Tocantins and a compilation of its Brazilian distribution - Roberto Novaes; Renan Souza; Saulo Felix; Gabriella Jacob; Cristal Sauwen; Leonardo Avilla (Check List, 2014)
The lesser spear-nosed bat, Phyllostomus elongatus, is endemic of South America and in Brazil this species is recorded in Amazon, Atlantic Forest, Cerrado, and Pantanal. Here, we present a new record for P. elongatus in the savanna of central Brazil, known as the Cerrado. In January 2012, five individuals of P. elongatus were captured and recorded in a limestone cave in the Aurora do Tocantins county, Tocantins State. Phyllostomus elongatus has already been registered in 32 locations and 14 Brazilian states, and their records appear to be associated with humid habitats and forested areas.